Crystal structure of citric acid–acetonitrile (1/1), C8H11NO7 - Liu Yang; Zheng Xiao-Yuan; Qin Liu-Lei; Zhu Chun-Li; Liu Zunqi (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C8H11NO7, triclinic, P1̄ (no. 2), a = 5.5944(13) Å, b = 10.402(3) Å, c = 10.666(3) Å, α = 110.297(2)o, β = 101.342(3)o, γ = 104.701(2)o, V = 534.6(2) Å3, Z = 2, Rgt(F) = 0.0318, wRref(F2) = 0.0833, T = 293(2) K.